4P Marketing Mix Strategy Samsung Galaxy Series A05 Smartphone Products - Olivia Yolanda; Rizki Nurul Nugraha (West Science Interdisciplinary Studies, 2024)
Technological developments and the push of the era of globalization are one of the main causes of transformation and development of sophisticated technology. Smartphones are one of the electronic products that humans need in their daily mobility, whose main function is as a communication tool and have various functional features such as sending messages, listening to music, browsing, taking photos or videos, and running software applications. Samsung is a brand that sells electronic products, one of which is smartphones. This research aims to review the 4P marketing mix strategy for the Samsung Galaxy Series A05 smartphone product. The research method used is descriptive qualitative with SWOC analysis. It can be concluded that the 4P marketing mix for the Samsung Galaxy Series A05 Smartphone product using the SWOC approach produces four alternative strategies, namely: SO; WO; SC; WC. Thus, the marketing mix for the Samsung Galaxy A05 seeks to position the Samsung Galaxy A05 as a competitive choice in the lower middle class by prioritizing a balance between feature performance and price. The Samsung company must maintain the quality of its products and brand image. Increasing innovative, varied, and consistent promotions. Then take advantage of affiliates and brand ambassadors who are known to potential consumers. Using a brand image that is already embedded in society, creates new trends to increase opportunities to compete. Then expand market share with the aim of attracting more consumers.